2023
DOI: 10.3390/diagnostics13030398
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Methyl-Enriched Diet Increases DNMT1, HCN1, and TH Gene Expression and Suppresses Absence Seizures and Comorbid Depression in Offspring of WAG/Rij Rats

Abstract: The reduced expression of the HCN1 ion channel in the somatosensory cortex (SSC) and mesolimbic dopamine deficiency are thought to be associated with the genesis of spike-wave discharges (SWDs) and comorbid depression in the WAG/Rij rat model of absence epilepsy. This study aimed to investigate whether the maternal methyl-enriched diet (MED), which affects DNA methylation, can alter DNMT1, HCN1, and TH gene expression and modify absence seizures and comorbid depression in WAG/Rij offspring. WAG/Rij mothers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Although few studies have examined the effects of MCS on hyperexcitability, our results showing the benefits of high choline are consistent with reports that a methyl-enriched diet (including choline but also betaine, folic acid, vitamin B12, l -methionine, and zinc) reduced spike wave discharges ( Sarkisova et al, 2023 ) and audiogenic seizure severity ( Poletaeva et al, 2014 ) in the offspring. Also, perinatal ethanol treatment that increased excitability was mitigated by choline chloride injection from postnatal days 10–30 ( Grafe et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although few studies have examined the effects of MCS on hyperexcitability, our results showing the benefits of high choline are consistent with reports that a methyl-enriched diet (including choline but also betaine, folic acid, vitamin B12, l -methionine, and zinc) reduced spike wave discharges ( Sarkisova et al, 2023 ) and audiogenic seizure severity ( Poletaeva et al, 2014 ) in the offspring. Also, perinatal ethanol treatment that increased excitability was mitigated by choline chloride injection from postnatal days 10–30 ( Grafe et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although few studies have examined the effects of MCS on hyperexcitability, our results showing the benefits of high choline are consistent with reports that a methyl-enriched diet (including choline but also betaine, folic acid, vitamin B12, L-methionine and zinc) reduced spike wave discharges in the offspring (Sarkisova et al, 2023) and audiogenic seizure severity (Poletaeva et al, 2014).…”
Section: Benefits Of High Cholinesupporting
confidence: 91%
“…These data indicate that treatment with methyl-group donors during neurodevelopment, which is the most sensitive period for epigenetic modifications, can exert long-lasting disease-modifying effects and, therefore, may represent a promising new approach to the treatment of depressive disorders related or unrelated to seizures. Here we have shown that short-term treatment of adult WAG/Rij rats with a methyl-group donor can be as effective in alleviating depression and associated absence seizures as early and long-term treatment [20]. The question of whether L-MET treatment causes a change in the expression of genes, including those related to the metabolism of monoamines in the brain, as well as what their epigenetic mechanisms are, awaits further research.…”
Section: Discussionmentioning
confidence: 87%
“…In our previous work, a maternal diet enriched with methyl-group donors and cofactors of the one-carbon cycle (choline, betaine, folic acid, vitamin B12, L-MET, zinc) during the perinatal period enhanced the DAergic tone of the brain mesolimbic system [72], increased the expression of selected genes potentially representing the cause of the pathology, and suppressed the occurrence of absence seizures and comorbid depression in adult offspring of the WAG/Rij rats [20]. SAMe treatment of pregnant submissive mice, as a model of depression, alleviated depressive-like behavioral symptoms and changed the level of brain monoamines and the expression of genes related to monoamine metabolism in adult offspring [73].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation